2017
DOI: 10.1080/15459624.2017.1365152
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of waste isoflurane gas exposure during rodent surgery in an Australian university

Abstract: Biomedical researchers use of inhalational anesthetics has increased in recent years. Use of isoflurane as an inhalational anesthetic may result in human exposure to waste anesthetic gas. Potential health effects from exposure include genotoxic and hepatotoxic effects with some evidence of teratogenic and reproductive effects. Research suggests that exposure to waste anesthetic gas within human hospital settings has improved substantially but exposures to biomedical researchers and veterinarians still requires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In a study conducted on experimental animals (rodents) anesthetized with isoflurane in a research laboratory, low residual anesthetic concentrations were observed, since the operating room was complying to Australian regulations, with appropriate ventilation and an effective gas exhaustion system and modern model of anesthesia machine, resulting in minimal exposure to anesthetics. 20 In a recent publication, research reports were reviewed retrospectively to evaluate isoflurane exposure in rooms used to perform surgical procedures in animals (primate, swine, and rodent) and in operating rooms where humans underwent surgery at the US National Institutes of Health. 21 Measurements were performed in operating rooms with a laminar flow system that produced 17 air changes per hour without recirculation and whose anesthesia machine also had a scavenging system connected to the central system of exhaustion of the hospital, with suctioning flow of 45 L.min -1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted on experimental animals (rodents) anesthetized with isoflurane in a research laboratory, low residual anesthetic concentrations were observed, since the operating room was complying to Australian regulations, with appropriate ventilation and an effective gas exhaustion system and modern model of anesthesia machine, resulting in minimal exposure to anesthetics. 20 In a recent publication, research reports were reviewed retrospectively to evaluate isoflurane exposure in rooms used to perform surgical procedures in animals (primate, swine, and rodent) and in operating rooms where humans underwent surgery at the US National Institutes of Health. 21 Measurements were performed in operating rooms with a laminar flow system that produced 17 air changes per hour without recirculation and whose anesthesia machine also had a scavenging system connected to the central system of exhaustion of the hospital, with suctioning flow of 45 L.min -1 .…”
Section: Discussionmentioning
confidence: 99%
“…There are some articles in the scientific literature discussing anesthetic pollution in veterinary surgical centers, but all were performed in developed countries and with different objectives. 14 , 16 , 17 , 18 , 19 , 20 , 21 …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the needed of equipment for inhalant anesthetic administration enhances the cost and reduces convenience of anesthesia. Further, the waste anesthetic gas leakage may be a occupational risk for researchers (Todd et al 2013;Johnstone et al 2017). From these raised points, it is patent that several factors must be taken into account for the choice of general anesthetic in each experimental design.…”
Section: Isoflurane Effectsmentioning
confidence: 99%
“…With the increasing availability of volatile anesthesia in rodents and apparent benefits compared to injectable anesthetics [ 15 , 16 ], there is an immediate need to describe methods providing safe and reliable use. However, conventional small animal ventilators can lead to high consumptions of volatile anesthetics and room air pollution when appropriate scavenger systems are missing [ 17 , 18 ]. Therefore, maintenance of anesthesia over several hours using volatile anesthetics may be inconvenient and results in unnecessary prolonged exposure of staff.…”
Section: Introductionmentioning
confidence: 99%